Microbial Communities on Plastic Polymers in the Mediterranean Sea - Vaksmaa, Annika; Knittel, Katrin; Abdala Asbun, Alejandro; Goudriaan, Maaike; Ellrott, Andreas; Witte, Harry J.; Vollmer, Ina; Meirer, Florian; Lott, Christian; Weber, Miriam; Engelmann, Julia C.; Niemann, Helge (Frontiers in Microbiology, 2021)
Plastic particles in the ocean are typically covered with microbial biofilms but it remains unclear whether distinct microbial communities colonise different polymer types. In this study, we analysed microbial communities forming biofilms on floating microplastics in a bay of the island of Elba in the Mediterranean Sea. Raman spectroscopy revealed that the plastic particles mainly comprised polyethylene, polypropylene and polystyrene of which polyethylene and polypropylene particles were typically brittle and featured cracks. Fluorescence in situ hybridisation and imaging by high resolution microscopy revealed dense microbial biofilms on the polymer surfaces. The 16S rRNA gene amplicon sequencing showed that the bacterial communities on all plastic types consisted mainly of the orders Flavobacteriales, Rhodobacterales, Cytophagales, Rickettsiales, Alteromonadales, Chitinophagales and Oceanospirillales. We found significant differences in the biofilm community composition on PE compared to PP and PS (but not between PP and PS), which shows that different microbial communities colonise specific polymer types. Furthermore, the sequencing data also revealed a higher relative abundance of archaeal sequences on PS in comparison to PE or PP. We furthermore found a high occurrence, up to 17% of all sequences, of different hydrocarbon-degrading bacteria on all investigated plastic types. However, their functioning in the plastic associated biofilm and potential role in plastic degradation needs further assessment.